A Clinical Study to Evaluate the Efficacy of Conductive Method of Agnikarma with Suvarnadi Salaka in the Pain Management of Sandhigatavata (Osteoarthritis of Knee Joint) - Ram Karan Saini; Rajesh Kumar Gupta (AYUSHDHARA, 2025)
The conductive method of Agnikarma using Suvarnadi Shalaka has proven to be an effective treatment for Sandhigata Vata (osteoarthritis of the knee joint), a degenerative disorder characterized by pain, stiffness, and restricted joint mobility. This clinical study aimed to evaluate the efficacy of Agnikarma in pain management and functional improvement. A total of 30 patients diagnosed with knee osteoarthritis were treated with conductive method of Agnikarma once a week for four weeks. The results demonstrated a significant reduction in pain (85.32%), tenderness (89.75%), and crepitus (78.35%), along with improvements in joint mobility (extension: 55.87%, flexion: 10.89%). Statistical analysis confirmed these findings as highly significant (p < 0.0001). The treatment was well tolerated with no major adverse effects, offering a safe, minimally invasive, and effective alternative to conventional therapies. Agnikarma works by improving local circulation, reducing inflammation, and enhancing tissue healing, making it particularly beneficial for Vata-Kaphaja disorders. This study concludes that the conductive method of Agnikarma with Suvarnadi Shalaka is a promising approach for managing knee osteoarthritis, with further large-scale studies needed to establish its long-term efficacy.